2018
DOI: 10.1093/aje/kwy047
|View full text |Cite
|
Sign up to set email alerts
|

Competing Effects of Indirect Protection and Clustering on the Power of Cluster-Randomized Controlled Vaccine Trials

Abstract: Power considerations for trials evaluating vaccines against infectious diseases are complicated by indirect protective effects of vaccination. While cluster-randomized trials (cRCTs) are less statistically efficient than individually randomized trials (iRCT), a cRCT's ability to measure direct and indirect vaccine effects may mitigate the loss of efficiency due to clustering. Within cRCTs, the number and size of clusters affects three determinants of power: the effect size being measured, disease incidence, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Cluster randomized trials (CRTs) have become a popular form of randomized trial, with many practical benefits, reflecting the necessity of implementing some interventions on clusters of individuals, and statistical benefits, such as accounting for interference between individuals . The causal estimand of interest and the overall risk‐benefit profile of the trial can also affect the choice to use cluster randomization . Although parallel‐arm CRTs are the most common, stepped wedge CRTs (SW‐CRTs) have also become more common, being used for a variety of interventions .…”
Section: Introductionmentioning
confidence: 99%
“…Cluster randomized trials (CRTs) have become a popular form of randomized trial, with many practical benefits, reflecting the necessity of implementing some interventions on clusters of individuals, and statistical benefits, such as accounting for interference between individuals . The causal estimand of interest and the overall risk‐benefit profile of the trial can also affect the choice to use cluster randomization . Although parallel‐arm CRTs are the most common, stepped wedge CRTs (SW‐CRTs) have also become more common, being used for a variety of interventions .…”
Section: Introductionmentioning
confidence: 99%
“…In order to further prepare in advance for epidemics, future work should characterize choices for specific pathogen characteristics and contexts. Mathematical modeling and simulation are useful tools for addressing choices beyond the four discussed here, e.g., sample size, trial location, duration, or end point [ 33 , 50 52 ]. Rigorous ethical analysis, as well as inclusive and transparent debate by different stakeholders, would help to illuminate the underlying moral questions.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, particular circumstances may weigh in favor of a cRCT. Recent work has shown that despite the larger sample size typically required in cRCTs compared to iRCTs because of the design effect (see glossary), in some settings, the difference in sample size may be modest, because the larger effect measured (indirect plus direct) in a cRCT partly offsets this effect [ 33 ]. Additionally, in some circumstances, an iRCT design may be logistically complex or may be unacceptable to the local population, which could threaten a trial’s successful completion—and thus its social and scientific value, essential to its justification [ 12 , 34 ].…”
Section: Randomized Vaccine Trial Design Choices During Epidemicsmentioning
confidence: 99%
“…Simulation approaches have been previously used to evaluate the statistical power of cRCTs evaluating vaccination at both individual and cluster scales 20 , 21 , 22 , 23 This allows investigators to size cRCTs to have a desired power to detect a specified true effect size of interest (ie, reduction in transmission). Although estimators have different properties and interpretations depending on the phase of the epidemic—for example, by capturing more indirect effects or having less impact when there is more preexisting immunity—this allows hypothesis tests to be appropriately powered.…”
Section: Introductionmentioning
confidence: 99%